Exploring cultural landscape narratives to understand challenges for collaboration and their implications for governance - Schaal-Lagodzinski, Tamara; König, Bettina; Riechers, Maraja; Heitepriem, Nico; Leventon, Julia (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
Ongoing land use change, including both land abandonment and agricultural intensification and expansion, not only present a threat for biodiversity and ecosystem health but also for the persistence of cultural landscapes. However, farmland abandonment and the resulting loss of traditional cultural landscapes is an under-researched topic in the literature. Our work in a transdisciplinary action research project in the Spreewald Biosphere Reserve suggested that challenges to preserve the cultural landscape are rooted in diverging landscape understandings and future aspirations. Dealing with and integrating different perceptions and viewpoints is a key challenge in landscape governance. Narratives as storylines about a topic or an issue have a structural and temporal dimension and can help understand land-use conflicts and different viewpoints. We adopted a social constructivist perspective on landscape to engage with meanings and perceptions (including values) that constitute landscape to diverse stakeholders. To understand these differences in meaning, we drew on Q-methodology and conducted 38 interviews with key stakeholders. We elicited three co-existing and partly overlapping landscape narratives. These differ with regard to meanings of the term cultural landscape, including how stakeholders characterise the landscape, how they appreciate it, and what they perceive as threats. We show how such differences in meanings and values attributed to the landscape translate to different problem framings and future aspirations and thus present a barrier for collaborative management and governance. We highlight how participatory vision development could help address narrative tensions and argue that a more integrative perspective would better include cultural aspects.
Keywords: Biodiversity; Biosphere Reserve; Plurality; Spreewald; Values; 333 Boden- und Energiewirtschaft